Effects of mango (Mangifera indica L.) and guava (Psidium guajava L.)extract on frozen chicken meat balls’ storage quality - Ali, Norhidayah; Babji, Abdul Salam; Md Sharif, Mohd Shazali; Md Nor, Norazmir; Hazali, Norazlanshah (Asian Network for Scientific Information, 2011)
A study was carried out to determine the effect of mango and guava extract on frozen Chicken Meat Balls (CMB) storage quality. CMB were added with four different formulations; mango extract (400 ppm); guava extract (800 ppm); synthetic antioxidant (BHA) (200 ppm) and a control group. Antioxidant activities, Total Phenolic Compound (TPC), Ferum (III)Reducing Power (FRAP) and Ferric Thiocyanate (FTC) were also analyzed. Determination of Thiobarbituric Acid (TBA) test and Peroxide Value (PV) were done on CBM samples which had been stored in -18oC for 0, 1, 2 and 3 months and sensory evaluation for 0 and 2 months. TPC showed that mango had higher value at 548.77 μg/100 g fresh weight compared to guava at 222.09 μg/100 g fresh weight. FRAP value significantly (p<0.05) indicated that mango extract able to reduce ferric ions more effectively compared to guava extract. FTC test significantly (p<0.05) showed that both mango and guava extracts efficient slowed down the oxidation process compared to control group after seven days of incubation. PV control group was significantly high (p<0.05); 3.38 meq/kg as compared to other formulation groups. TBA analysis showed that mango and guava extract able to inhibit the oxidation process which similar to BHA. In conclusion, additional mango and guava extract did not affect on frozen CBM storage quality and consumers’ acceptance.